From Hispalis to Ishbiliyya : the ancient port of Seville, from the Roman empire to the end of the Islamic period (45 BC-AD 1248) - Cabrera Tejedor, Carlos, 1976- (Archaeopress Publishing Ltd., 2019)
This monograph focuses on the history and development of the topography, layout, and facilities of the ancient port of Seville, located in the lower Guadalquivir River Basin, between the 1st century BC and the 13th century AD. Until now, despite its commercial importance, little has been known about the port's exact position, layout, and facilities.